Theoretical Analysis Of The Photon Production Rate in the Quark-Gluon Interaction According To The Quantum Cromodynamic QCD Theory - Mustafa Hussein, Saba; AL-Agealy, Hadi J. M.; Al-Rubaiee A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this work, we have used the QCD dynamic scenario of the quark gluon interaction to investigate and study photon emission theoretically based on quantum theory. The QCD theory is implemented by deriving the photon emission rate equation of the state of ideal QGP at a  chemical potential. The photon rate of the quark-gluon interaction has to be calculated for the anti up-gluon interaction in the g →  γ system at the temperature of system  with critical temperature ( 132.38, ,  and 198.57) MeV and photon energy (  GeV. We investigated a significant effect of critical temperature, strength coupling, and photon energy on the photon rate contribution. Here, the increased photon emission rate and decreased strength coupling of the quark-gluon reaction due to the decrease in temperature of the system from 360 MeV to 180 MeV are predicted. Photon energy in the range (1 to 10) GeV and the rate spectrum of four varieties of critical temperatures are presented. The interesting point in our results is the minimum value of photon rate, especially in the photon energy E=10 GeV of  ﬂavor which reflects the poor coupling between quark and gluon  in the the g →  γ system which was already expected. The features of QCD  results are  achieved in the case of  ﬂavors for the photon energy E=1 to 10 GeV, the strength coupling and the photo meason rate are calculated theoretically. We can notice that the asymptotic behavior, which was characterized by a hadronic phase limit, will be satisfied.